Knowledge, Attitude and Perception of Undergraduate Medical Students on Medico-Legal Autopsies (Community Based Medical Journal, 2026)
A descriptive, cross-sectional study was conducted in the Department of Forensic Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from September 2023 to February 2025, to evaluate the knowledge, attitudes, and perceptions of undergraduate medical students regarding medico-legal autopsies, exploring the impact of forensic medicine education on their understanding and appreciation of autopsies in future medical practices. A total of 105 students from third to fifth year of the MBBS program were selected through convenient sampling. Before data collection consent was taken and confidentiality was strictly maintained. Data was collected through a semi-structured, pre-tested questionnaire. The mean age of participants was 22.26±1.12 years, with most in the 21–22 years age group (68.6%). Gender distribution was nearly balanced (51.4% male and 48.6% female). A significant portion of respondents (73.3%) demonstrated knowledge of the purpose of autopsies, while 88.6% recognized the necessity of postmortem examinations in all unnatural deaths (P